2020
DOI: 10.3390/nu12072116
|View full text |Cite
|
Sign up to set email alerts
|

Earlier Nutrient Fortification of Breastmilk Fed LBW Infants Improves Jaundice Related Outcomes

Abstract: This study aimed to evaluate jaundice outcomes of low-birthweight premature infants commenced on earlier versus later nutrient supplementation (80 mL/kg/day vs. 160 mL/kg/day; total fluid intake, F80 vs. F160). Demographics, feeding regimens, and clinical outcomes data were collected. Infant and maternal characteristics were similar. Earlier nutrient supplementation was associated with multiple improved jaundice outcomes: total (TSBR), unconjugated and conjugated (CSBR) serum bilirubin values (196 ± 46 vs. 228… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Hyperbilirubinemia was chosen as a balancing measure due to the impact feeding has on bilirubin excretion. There is a known association between poor enteral intake or dehydration as well as the timing of enteral feedings and the development of hyperbilirubinemia 14-16. The late preterm infant is at a higher risk of developing physiologic jaundice due in part to the degradation of red blood cells and limited ability of the liver to conjugate bilirubin as well as the enterohepatic circulation of unconjugated bilirubin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperbilirubinemia was chosen as a balancing measure due to the impact feeding has on bilirubin excretion. There is a known association between poor enteral intake or dehydration as well as the timing of enteral feedings and the development of hyperbilirubinemia 14-16. The late preterm infant is at a higher risk of developing physiologic jaundice due in part to the degradation of red blood cells and limited ability of the liver to conjugate bilirubin as well as the enterohepatic circulation of unconjugated bilirubin.…”
Section: Methodsmentioning
confidence: 99%
“…There is a known association between poor enteral intake or dehydration as well as the timing of enteral feedings and the development of hyperbilirubinemia. [14][15][16] The late preterm infant is at a higher risk of developing physiologic jaundice due in part to the degradation of red blood cells and limited ability of the liver to conjugate bilirubin as well as the enterohepatic circulation of unconjugated bilirubin. The American Academy of Pediatrics guidelines and nomograms were followed to determine the threshold for phototherapy.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…19 Breast milk is known to contain betaglucuronidase, which in the intestine, decouples glucuronic acid from conjugated bilirubin and allows bilirubin to be reabsorbed by the enterohepatic circulation. 23 Breast milk jaundice first becomes visible on the face and progresses to the trunk and then the extremities around the first weeks of life and may last up to 3 months. 19−21 The jaundice is not actively treated unless the total serum bilirubin level of the infant is greater than 20mg/dL, when phototherapy may be employed.…”
Section: Neonatal Integumentary Changesmentioning
confidence: 99%
“…Newman et al ( 20 ) first reported that breastmilk was a contributing factor to the development of neonatal jaundice. Breastmilk contains the substance beta-glucuronidase, which, in the intestine, decouples glucuronic acid from conjugated bilirubin and allows bilirubin to be reabsorbed by the enterohepatic circulation ( 21 ). In addition, bilirubin undergoes selective metabolism by UDP-glucuronosyltransferase (UGT) 1A1, that UGT1A1 gene mutation is closely related to BMJ ( 22 , 23 ).…”
Section: Bmj Influences Breastfeedingmentioning
confidence: 99%